ANALISIS TINGKAT KESEHATAN BANK CAMPURAN DAN BANK ASING DI MASA KRISIS - Nazrantika Sunarto; Suharyono Suharyono (Politeknik Negeri Bengkalis, 2016)
Abstract: The global economic crisis has led various global financial ins- titutions suffered losses. Banking ratio measurement is useful to assess the risk base bank rating and growth of banking. This study aims to determine whether there are significant differences between risk base bank rating of foreign banks and joint venture banks before the global crisis until after the global crisis. The risk base bank rating is measured using the ratio of CAMEL. Total population consisted of 23 banks; 15 joint venture banks and 8 foreign banks. In hypothesis testing, different test of Mann Whitney was used. The research proved that the risk base bank rating of foreign banks and joint venture banks before and during the global crisis, during and after the global crisis, and before and after the glo- bal crisis did not have a significant difference. Keywords: CAMEL, Foreign, Joint Venture, Banks, Crisis.